Keeping up with influencers: exploring the impact of social presence and parasocial interactions on Instagram. Issue 3 (22nd April 2022) - Kim, Hyosun
Abstract: An experiment was conducted to examine the level of social presence and the mediating role of parasocial interaction in influencer marketing. In a simulated fitness influencer's Instagram posts, social presence significantly predicts individuals' purchase intent toward the brand featured in the posts as well as self-efficacy, working through parasocial interactions. Parasocial interaction with influencers serves as a mediator, while influencers can act as role models to motivate people to take action and benefit the brand by encouraging consumers to purchase the products featured in their posts. Higher social presence in the posts led individuals to feel that the posts were less promotional. The effect of parasocial interaction was moderated by advertising recognition, such that lower social presence posts appeared to suggest a promotional appeal and negatively affected purchase intent. Thus, social presence and parasocial interaction are key predictors of successful influencer marketing, yet they can pose a concern because they may hinder consumers from developing accurate persuasion knowledge.